Since f(g(x)) = g(f(x)) = x, hence the function f(x) and g(x) are inverses of each other.
<h3>Inverse of functions</h3>
In order to determine if the function f(x) and g(x) are inverses of each other, the composite function f(g(x)) = g(f(x))
Given the function
f(x)= 5-3x/2 and
g(x)= 5-2x/3
f(g(x)) = f(5-2x/3)
Substitute
f(g(x)) = 5-3(5-2x)/3)/2
f(g(x)) = (5-5+2x)/2
f(g(x)) = 2x/2
f(g(x)) = x
Similarly
g(f(x)) = 5-2(5-3x/2)/3
g(f(x)) = 5-5+3x/3
g(f(x)) = 3x/3
g(f(x)) =x
Since f(g(x)) = g(f(x)) = x, hence the function f(x) and g(x) are inverses of each other.
Learn more on inverse of a function here: brainly.com/question/19859934
#SPJ1
Answer:
exact form:
9/2
decimal form:
4.5
mixed number form:
4 1/2
Step-by-step explanation: sorry if this wasnt what you were looking for.
The answer is 90 + 45 because BOC is a right angled triangle where angle BOC is 90 and angle BOK is 45 because 90 ÷2. A OK Is a right angled triangle so angle AOB is 90 as well so to find angle AOK we plus 90 and 45 which is 135 degrees.
The statement will be m∠ABC = m∠GHI.
Reason: ∠ABC ≅ ∠GHI
13 feet wide.
156/12=13
Brainliest plz